Gratitude-Based Community Counseling Service Program In Improving Subjective Well-Being Of Acehen Students Experiencing Social Anxiety - Azizunnisa, Amelia; Arifin, Isep Zaenal; Kusnawan, Aep (Educational Guidance and Counseling Development Journal, 2025)
The main objective of this study was to identify the social anxiety and subjective well-being of Acehnese students living abroad in Bandung City, and to design a gratitude-based community counseling service program to address these issues. This study employed an interpretive paradigm with descriptive qualitative methods and a phenomenological approach. Data were collected through observation, in-depth interviews, and documentation, with data sources coming from the Chairperson, Members, and Alumni of the PANGLIMA community.The results of the study showed that the social anxiety experienced by Acehnese students living away from home varied, characterized by difficulty adapting, feelings of inferiority, fear of being judged negatively, language barriers, and a tendency to withdraw from social interactions.Factors influencing this anxiety include cultural and language differences, academic pressure, and self-perception of their hometown. Students' subjective well-being also varied from low to moderate, with some reporting limited life satisfaction and positive emotions. Factors influencing subjective well-being include social support from family and community, academic achievement, and the ability to manage negative emotions such as loneliness and stress. A gratitude-based community counseling program was designed to address these issues, emphasizing self-reflection, gratitude training, communal prayer, and strengthening social support. This program is expected to reduce social anxiety levels while improving subjective well-being among students living away from home.